An HLA-C amino-acid variant in addition to HLA-B*27 confers risk for ankylosing spondylitis in the Korean population - Kim, Kwangwoo (Arthritis Res Ther, 2015)
INTRODUCTION: The presence of the HLA-B*27 allele is a major risk factor for the development of ankylosing spondylitis (AS), which causes chronic inflammation of the spine and other sites. We investigated residual effects outside HLA-B within the major histocompatibility complex (MHC) region in the Korean population. METHODS: Using the Korean HLA reference panel, we inferred the classic HLA alleles and amino-acid residues of the six HLA genes (HLA-A, -B, -C,-DPB1, -DQB1, and -DRB1) and MHC single-nucleotide polymorphisms in 3820 Korean subjects, including 654 Korean cases of AS and 3166 controls, who were genotyped by using Immunochip. Logistic regression and log-likelihood ratio tests were used in AS association tests for imputed markers. RESULTS: The most significant associations were identified at amino-acid positions in the epitope-binding site of HLA-B (P = 1.71 × 10(−481) at position 70, P = 7.20 × 10(−479) at position 97, and P = 2.54 × 10(−484) at positions 114), highlighting the risk effect of the HLA-B*27 allele and the protective effects of other classic alleles. A secondary effect was located at the leucine at amino-acid position 116 in the epitope-binding site of HLA-C (P = 1.69 × 10(−14)), completely tagging the HLA-C*15:02 allele. This residue had a large effect in HLA-B*27-negative patients (odds ratio = 6.6, 95 % confidence interval = 3.8 to 11.4). CONCLUSIONS: The four amino-acid positions of HLA-B and -C account for most of the associations between AS and MHC in the Korean population. This finding updates the list of AS susceptibility loci and provides new insight into AS pathogenesis mediated by MHC class I molecules. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s13075-015-0855-3) contains supplementary material, which is available to authorized users.